IN VITRO ANTIMICROBIAL, INSECTICIDAL, CYTOTOXIC ACTIVITIES AND THEIR PHYTOCHEMICAL ANALYSIS OF METHANOLIC EXTRACT AND ITS FRACTIONS OF PEUCEDANUM BELUCHISTANICUM LEAVES - NIZAM BALOCH; ABDUL MANAN KAKAR; SAJID NABI; MASOOM YASINZAI; DR. YASSER M.S.A. AL-KAHRAMAN (International Journal of Pharma and Bio Sciences, 2013)
The aim of the present investigation deals with biological evaluation Peucedanum Beluchistanicum leaves. For this purpose different biological assay of methanolic extract (Crude) and its fractions that are chloroform fraction, n-hexane fraction, Ethyl acetate fraction, n-butanol fraction and aqueous fraction were carried out. The results from the agar diffusion method indicated that Crude showed maximum antibacterial activity against Staphylococcus aureus with the inhibition zone (28.3±0.04mm). Whereas Ethyl acetate fraction also showed strong activity against Staphylococcus aureus (25.2±0.9mm). On the other hand, Crude showed maximum activity against Candida albicans and Candida glaberata with % inhibition of (73±0.4%) and (68±0.2 %) respectively and Chloroform fraction showed good activity against Candida albicans with % inhibition of (62±0.12%). Furthermore, Crude showed maximum insecticidal % mortality against Tribolium castaneum with (86%) mortality whereas (80%) mortality against Rhyzopertha dominica. and also Chloroform fraction also showed maximum activity against Tribolium castaneum with (70%) mortality. Moreover Chloroform fraction showed significant Cytotoxic activity with ED50 value 0.85 µg//ml and Crude showed Cytotoxic activity with ED50 value 0.98 µg//ml. Furthermore, the phytochemical analysis of Crude and its fractions showed the presence of Alkaloids, Flavonoids, Phenols, Saponins and Diterpenes.